(untitled) (World Bulletin of Public Health, 2025)
The article presents the results of an analysis of surgical treatment in 193 patients with acute colonic obstruction observed during the period 2000– 2022. The main cause of obstruction in 83.9% of cases was colon tumors. The authors examine various surgical approaches for right- and left-sided tumor-related colonic obstruction, including hemicolectomy, subtotal colectomy, Hartmann’s procedure, and primary anastomosis. Special attention is given to intraoperative methods of bowel decompression (cecostomy, appendicostomy), which help reduce postoperative complications. It is shown that timely surgical intervention and an individualized tactical approach—based on the anatomical and functional condition of the bowel wall and comorbidities—improve treatment outcomes. Postoperative mortality was 16%, mainly in patients over 65 years of age, which is associated with delayed admission, intoxication, and significant metabolic disturbances. The authors conclude that primary radical surgery is advisable in cases of tumor-related colonic obstruction, as it eliminates the source of intoxication and prevents further progression of the disease